How E-Learning Affects Students' Mental Health During Covid-19 Pandemic: An Empirical Study - Siti Fatimah; Umi Mahmudah (Universitas Sebelas Maret, 2020)
This study aimed to determine the impact of e-learning on the Indonesian students’ mental health during the COVID-19 pandemic. The subjects in this study were 210 respondents, namely students at the junior high school, senior high school, and university levels. The instrument used was both closed and open questionnaire sheets. The data analysis technique was multiple linear regressions using the Ordinary Least Square (OLS) method. The analysis shows that: 1) e-learning has a positive and significant effect on mental health; 2) age has a positive but is not statistically significant effect on mental health; and 3) gender has a negative but is not statistically significant effect on mental health.